2014
DOI: 10.1371/journal.pone.0101283
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping Cancer-Associated Genes in Chordoma Identifies Mutations in Oncogenes and Areas of Chromosomal Loss Involving CDKN2A, PTEN, and SMARCB1

Abstract: The molecular mechanisms underlying chordoma pathogenesis are unknown. We therefore sought to identify novel mutations to better understand chordoma biology and to potentially identify therapeutic targets. Given the relatively high costs of whole genome sequencing, we performed a focused genetic analysis using matrix-assisted laser desorption/ionization-time of flight mass spectrometer (Sequenom iPLEX genotyping). We tested 865 hotspot mutations in 111 oncogenes and selected tumor suppressor genes (OncoMap v. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
54
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 41 publications
4
54
1
1
Order By: Relevance
“…A common cause for EGFR activation is the presence of mutations and gene amplification, as seen in non‐small cell lung cancer and glioblastoma . However, this is not the case for the cell lines in our study, which is consistent with published EGFR genetic profiling reports and the unpublished data from ∼30 whole genomes/whole exomes from our laboratory. The absence of EGFR mutations in chordomas is shared with other cancers, such as head and neck squamous cell carcinoma and colorectal and pancreatic cancers, which are known to respond to anti‐EGFR therapy to varying degrees .…”
Section: Discussionsupporting
confidence: 92%
“…A common cause for EGFR activation is the presence of mutations and gene amplification, as seen in non‐small cell lung cancer and glioblastoma . However, this is not the case for the cell lines in our study, which is consistent with published EGFR genetic profiling reports and the unpublished data from ∼30 whole genomes/whole exomes from our laboratory. The absence of EGFR mutations in chordomas is shared with other cancers, such as head and neck squamous cell carcinoma and colorectal and pancreatic cancers, which are known to respond to anti‐EGFR therapy to varying degrees .…”
Section: Discussionsupporting
confidence: 92%
“…The principal treatment of chordoma is radical surgical resection, augmented by adjuvant radiotherapy 2 . Chordoma does not respond to cytotoxic chemotherapy 3 . Most patients cannot be cured 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Chordoma does not respond to cytotoxic chemotherapy 3 . Most patients cannot be cured 3 . They often suffer from the debilitating consequences of tumour progression and its surgical treatment before dying from their disease 3 .…”
Section: Introductionmentioning
confidence: 99%
“…We found that the tumor suppressor p16 (CDKN2A) is deleted and that p16 protein is not expressed in these cell lines. This deletion has been described in the majority of chordomas (25)(26)(27). The downstream machinery of p16 can be efficiently inhibited by CDK4/6 inhibitors such as palbociclib (28).…”
Section: Introductionmentioning
confidence: 99%